Kekerasan Seksual Dalam Hukum Pidana Di Lingkungan Perguruan Tinggi - Ririn Nurfaathirany; Heri Tahir; Firman umar; Andika Wahyudi Gani; Aulia Raihanah Salwa Ardani (Universitas Negeri Makassar, 2023)
Sexual violence that occurs in a university environment is a different matter when compared to sexual violence within the scope of criminal law. Sexual violence is an urgent matter which is regulated separately in Minister of Education and Culture Regulation Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments, and there is a need to equalize perceptions regarding sexual violence in higher education environments. Based on this, the aim of this service is to provide adequate understanding of sexual violence in the tertiary environment, so that awareness for preventing sexual violence can be implemented optimally. The methods used in implementing this service are observation, counseling and evaluation. This service activity increases knowledge for lecturers, staff, students and campus residents regarding the types of sexual violence, the subjects involved, and the threat of sanctions against perpetrators of sexual violence.